2011
DOI: 10.1136/ard.2011.152769
|View full text |Cite
|
Sign up to set email alerts
|

Risk of septic arthritis in patients with rheumatoid arthritis and the effect of anti-TNF therapy: results from the British Society for Rheumatology Biologics Register

Abstract: ObjectivesTo evaluate the risk of septic arthritis (SA) in patients with rheumatoid arthritis (RA) treated with anti-tumour necrosis factor (TNF) therapy.MethodsUsing data from the British Society for Rheumatology Biologics Register, a prospective observational study, the authors compared the risk of SA between 11 881 anti-TNF-treated and 3673 non-biological disease-modifying antirheumatic drug (nbDMARD)-treated patients.Results199 patients had at least one episode of SA (anti-TNF: 179, nbDMARD: 20). Incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
21

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(116 citation statements)
references
References 21 publications
3
90
0
21
Order By: Relevance
“…Despite the clinical efficacy of anti-TNF therapies and a generally reassuring safety profile, some concerns remain regarding their long-term use due to the increased incidence of serious infections, tuberculosis (10,11), and potential malignancies (12). The cost of anti-TNF therapy is also an important consideration and leads to restrictions on prescribing in many countries (13).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clinical efficacy of anti-TNF therapies and a generally reassuring safety profile, some concerns remain regarding their long-term use due to the increased incidence of serious infections, tuberculosis (10,11), and potential malignancies (12). The cost of anti-TNF therapy is also an important consideration and leads to restrictions on prescribing in many countries (13).…”
Section: Introductionmentioning
confidence: 99%
“…5 Galloway et al 6 reported that exposure to TNF blocker therapy was associated with an increased risk of joint infection in patients with RA. This risk was greatest in the first year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The risk did not differ significantly between the three agents: infliximab (IFX), etanercept (ETN) and adalimumab (ADA). The hazard for SA in the anti-TNF cohort was greatest in the early months of therapy, as well as data from other cohorts [12], and the risk then decreased steadily over the remainder of the follow-up period [11]. One of the potential explanations for early increased risk is that it may reflect a true reduction in risk of joint infection in patients who achieve better control of their RA [11].…”
Section: Risk Of Septic Arthritis (Sa) In Ra Patientsmentioning
confidence: 99%
“…Galloway et al [11] conducted a prospective observational study to evaluate the risk of SA in patients with RA treated with anti-TNF-α agents. They reported that incidence rates for SA were anti-TNF 4.2/1000/patient years (95% CI 3.6-4.8) and nbDMARDs 1.8/1000/ patient years (95% CI 1.1-2.7).…”
Section: Risk Of Septic Arthritis (Sa) In Ra Patientsmentioning
confidence: 99%